Phoretic behaviour of attacobius attarum (Roewer, 1935) (Araneae: Corinnidae: Corinninae) dispersion not associated with predation? - Camargo, Roberto da Silva [UNESP]; Forti, Luiz Carlos [UNESP]; Oliveira de Matos, Carlos Alberto [UNESP]; Brescovit, Antonio D. (Taylor & Francis Ltd, 2015)
Attacobius attarum spiders exhibit a phoretic behaviour on the winged sexual of Atta leaf-cutting ants during their mating flight. However, it is unclear if this behaviour is for dispersion or to facilitate the predation of ants in the new colonies. A nest of Atta sexdens was monitored on the day of the mating flight, and the winged ants, as well as the spiders, were collected. The results obtained corroborate the hypothesis that phoretic behaviour is commonly used for dispersion of the spider A. attarum, predominantly females. Of these spiders, 64 individuals of A. attarium were collected, of which 62 were females (96.9%) and two were males (3.1%). Regarding the winged leaf-cutting ants sampled, 378 females and 361 males were collected, totaling 739 individuals. Of these, 64 individuals (8.7%) had a spider attached to its back for phoretic dispersal and none was observed on the queens after the nuptial flight. In our study, A. attarum females perform phoretic dispersal into the environment on winged leaf-cutting ants but do not settle in the new nests.
Keywords: Leaf-cutting ants; Phoresy; Spider; Atta sexdens